Indentification of Causes of Scabies on Santri of Popular Dayah Educational Institutions in Aceh Province - Evi Dewi Yani; Husna Husna; Masyudi Masyudi; T. M. Rafsanjani (JURNAL SERAMBI ILMU, 2022)
Scabies is an infection with mites (Sarchoptes scabies) that cause small red bumps on the skin. Scabies is caused by poor personal hygiene. Scabies or scabies disorders always start from itching on the skin caused by the scabies mite (Coptes scabei), transmission of scabies lice can occur due to direct transmission, for example in contact with sufferers or indirectly, such as through clothing, blankets, and towels. This study aims to analyze the factors that influence the incidence of scabies in traditional dayah santri in Aceh Besar district. The research was conducted using a qualitative method with the respondents of traditional dayah students in Aceh Besar. data on sanitation, bathrooms, toilets, room area, room humidity were carried out by ethnographic observations and direct interviews. The results of the qualitative research and direct observation in the dayah showed that the sanitation facilities were still inadequate in the dayah. Such as the number of occupants in one room which reaches more than 8 people in a room measuring 4 x 4 meters. Poor sanitation also seems to play a major role in the incidence of scabies in students. In addition, the personal hygiene behavior of students such as changing towels and bathing facilities which are less in number when compared to the number of students also accelerates the spread of scabies.